Openbaring en tolerantie: Actualiteit en toekomst van de politieke theologie - Erp, Stephan van (Tijdschrift voor theologie, 2008)
This essay contributes to the debate about the tasks and content of political theology. Political theology has become marginal in the last few decades, because of cultural and theological reasons. The essence of the problem of political theology is the cultural dilemma of religious pluralism and universality. Apart from this broader cultural dilemma, the author is of the opinion that theologians have difficulty entering political debates because of the evaporation of dogmatics and of the rigid separation of ethics and dogmatics. Against neo-orthodox theologies, he argues that this analysis does not necessarily have to lead to an anti-modern or anti-secular standpoint. A discussion of the problem of tolerance in current politics shows that dogmatic theology could find new material for political theology in the practice of tolerance and democracy. The history of tolerance teaches that theological arguments were used to support the practice of tolerance, long before enlightenment philosophers hijacked it as their own invention to criticise religious authorities. After an analysis of the reasons why a relationship between modern politics and religion in a pluralist context is far from self-evident, the solutions of multiculturalism and exclusivism are criticised. Theologies of particularity offer no answers to the dilemma of pluralism and universality. Instead, the democratic process and the call for tolerance could be regarded as the truth at work in a secularised culture. In the final section of this essay, the author proposes three aspects for a future political theology: a. traditions as inspiration; b. formation of communities and identities; c. legitimacy and representation. The last aspect offers the opportunity to rethink the theological concepts of revelation and the kingdom of God as an event and a space that enable the acknowledgement of the diversity of religious life without sacrificing the ideas of and faith in universality and truth.